2010
DOI: 10.1109/tgrs.2009.2034980
|View full text |Cite
|
Sign up to set email alerts
|

Development of the TanDEM-X Calibration Concept: Analysis of Systematic Errors

Abstract: The TanDEM-X mission, result of the partnership between the German Aerospace Center (DLR) and Astrium GmbH, opens a new era in spaceborne radar remote sensing. The first bistatic satellite synthetic aperture radar mission is formed by flying TanDEM-X and TerraSAR-X in a closely controlled helix formation. The primary mission goal is the derivation of a high-precision global digital elevation model (DEM) according to High-Resolution Terrain Information (HRTI) level 3 accuracy. The finite precision of the baseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 12 publications
1
58
0
Order By: Relevance
“…The residual phase trend is caused by small errors in the satellite positions, which result in baseline errors. Similar trends have been reported by other authors [6,15,16,21,49]. The error is easily observed in overlapping areas between adjacent swaths and can be corrected, to first order, by fitting an error model to the data.…”
Section: Scenes With Phase Trendssupporting
confidence: 88%
“…The residual phase trend is caused by small errors in the satellite positions, which result in baseline errors. Similar trends have been reported by other authors [6,15,16,21,49]. The error is easily observed in overlapping areas between adjacent swaths and can be corrected, to first order, by fitting an error model to the data.…”
Section: Scenes With Phase Trendssupporting
confidence: 88%
“…The expected root-mean-square error (RMSE) for the ASTER GDEM depends on topography and number of observations available, ranging from 3 to 50 m (Reuter et al, 2009;Hirt et al, 2010;Hengl and Reuter, 2011). The TanDEM-X DEM is expected to provide 10 m absolute and 2-4 m relative vertical accuracy (Gonzalez et al, 2010). ICESat altimeter data are accurate to ∼ 0.3 m in the vertical (Magruder et al, 2007).…”
Section: Digital Elevation Model (Dem)mentioning
confidence: 99%
“…The third mode is adopted in this study, as it is commonly used in monitoring land masses, whereas the other two are not designed for DEM generation. It is reported that the absolute vertical height specification accuracy of TSX/TDX DEM is 10 m (90% linear error), and the relative accuracy is ~2 m for areas with predominant terrain slopes that are smaller than 20° [27,37,40,41].…”
Section: Terrasar-x/tandem-xmentioning
confidence: 99%
“…Absolute height accuracy is a common criterion to assess InSAR DEMs based on the accurate traditional outcomes, such as GPS and LiDAR [40,41]. However, in some areas, ground control points is lacking or difficult to collect.…”
Section: Relative Height Accuracymentioning
confidence: 99%
See 1 more Smart Citation